Movement Patterns of Commuterline Users in the Medan City Train Station Area Based on Transit-Oriented Development Concept - Fidyan Aulia Nasution; Dyah Titisari Widyastuti (Built Environment Studies, 2021)
At the time of this research, Medan City was threatened with the gridlock, a situation where the number of vehicles exceeds the available road capacity. To prevent the gridlock happens, Medan Train Station (Medan ts.) area as the center activity of Medan City, will be developed into an area based on the Transit-Oriented Development (TOD) concept by adding Light Rail Transit (LRT) and Bus Rapid Transit (BRT). The addition is hoped to encourage walking and public transportation usage for visitors in Medan ts. area. This study aims to determine and mapping the movement patterns of commuterline users, in this case Medan – Binjai line which is the only line available, as the basis for the application of the concept of TOD in the Medan ts. area. The research uses observation and interview as the methods. The results of the study showed that the majority of commuterline users of the Medan ts. relied on paratransit when heading or leaving the station than walking. This can be seen from 70% of users (weekday) and 83.3% of users (weekends) using paratransit when heading to the station and 86.6% of users (weekday) and 66.6% of users (weekends) using paratransit when leaving the station.